Analisis Penjadwalan Proyek menggunakan Metode Critical Path Method (CPM) dan Project Evaluation Review Technique (PERT) (Studi Kasus Train Door pada Kereta Ukur MYC 2020 di PT INKA Multi Solusi) - Dinda Septi Ayuningtyas; Renanda Nia Rachmadita; Thina Ardliana (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Abstract - Train door is one of the projects undertaken by PT INKA Multi Solusi. This project was expected to be completed on time, but actually it was delayed. The methods used in this research are the Critical Path Method (CPM) and Project Evaluation Review Technique (PERT). The CPM and PERT methods are suitable for scheduling in order to obtain the fastest completion time by considering the estimated completion time of the project due to the uncertainty that occurs in the field, so that the percentage of possible completion of the project is obtained. The results found that the probability of delays in the planned schedule is 61.41%. To overcome this delay, it is necessary to accelerate the duration using an alternative 4 hours of overtime. Based on the analysis of the Time Cost Trade Off method, the optimal time and cost of the train door's production on the MYC 2020 measuring train's project was obtained, namely the acceleration of duration to 199.6 days with total cost of Rp 462,280,692,-. Based on the Swent under the curve of the plan duration because the completion process was delayed so the time required was longer than the plan.